Association of Metabolic Syndrome and Risk or Development of Chronic Kidney Disease: A Comprehensive Systematic Review - Setiawan Nathan, Daniel; Yumilia, Hoo (The International Journal of Medical Science and Health Research, 2024)
Background: Metabolic syndrome (MetS) encompasses a cluster of metabolic abnormalities including hypertension, hyperlipidemia, hyperuricemia, hyperglycemia, central obesity, and insulin resistance. MetS and chronic kidney disease (CKD) are intricately linked and can influence each other. This study aims to serve a comprehensive systematic review to evaluate the association of MetS and CKD in literatures of the last 10 years.   Methods: The review adhered to PRISMA 2020 standards and analyzed full-text English literature from 2014 to 2024. It excluded editorials, review papers from the same journal, and submissions lacking a DOI. Literature sources included PubMed, SagePub, SpringerLink, and Google Scholar. Result: A total of 488 articles were retrieved from online databases (PubMed, SagePub, SpringerLink and Google Scholar). After three rounds of screening, five articles directly relevant to the systematic review were selected for full-text reading and analysis. Conclusion: The discussion emphasizes the complex link between metabolic syndrome (MetS) and chronic kidney disease (CKD), driven by modern lifestyle habits causing metabolic overload. Kidneys are especially susceptible to MetS effects, but effective treatment strategies are lacking. Further research is needed to understand and address MetS-related kidney damage.